PPDM: Menjadikan Semarapura Kaja Sebagai Wisata Terintegrasi - Ni Made Jaya Senastri; Putu Suyatna Yasa; A A Rai Sita Laksmi (Postgraduated Community Service Journal, 2022)
The implementation of the Partner Village Development Program in Semarapura Kaja Village aims to empower the community in order to realize Semarapura Kaja Village as an Integrated Tourism. In order to achieve this goal, the program of activities is directed at the field of tourism promotion and marketing. Partner problems include: (1) There is no guide book for local guides in communicating in English, (2) There is no form of information in the form of nameplates and documents about cultural heritage in Semarapura Kaja Village, (3) public facilities in the form of MCK in the Market Besang Kangin is damaged so that it has not functioned optimally, (4) The management and marketing of MSMEs in Semarapura Kaja Village has not been maximized, (5) The website-based administrative service system has not been socialized. The five programs that were successfully implemented were: Installation of an integrated Tourism Signboard, Submission of a Tour Guide Book to Pokdarwis, Delivery of Public Service Innovation products in the form of E-PAK Application Design, Launching of Semarapura Kaja Village as integrated tourism, and Delivery of MCK Renovation Assistance. The outputs produced are articles in national journals with ISSN, publications in print/online media, increasing competitiveness, increasing the application of science and technology, and improving values in society.